Natural Compounds with Antimicrobial Properties in Cosmetics - Kamila Rybczyńska-Tkaczyk; Anna Grenda; Anna Jakubczyk; Kaja Kiersnowska; Marta Bik-Małodzińska (Pathogens, 2023)
Currently, the cosmetic industry is a very intensively growing part of the economy. Consumer demands are adapted to the current lifestyle, which is based on technological innovations and awareness of the impact of various factors on human health and fitness. There is growing interest in cosmetics based on environmentally friendly natural compounds exerting health-promoting effects. Chemicals with antimicrobial properties used as ingredients in cosmetics ensure their durability and safety. Polyphenolic compounds, peptides, essential oils, and plant extracts characterized by these properties are natural ingredients that can replace synthetic components of cosmetics. The advantage of these compounds is that they exhibit antioxidant, anti-inflammatory, and soothing properties, enhancing the product value in addition to their antimicrobial properties. This review article describes the antimicrobial properties of natural compounds that can protect cosmetics and can replace previously used preservative agents. Various studies indicate that the use of these compounds increases consumer interest in these products and has a positive impact on the environment.